Bioética, ecología y género - Velayos Castelo, Carmen (2013)
Bioethics is best known and institutionalized clinical bioethics. Some authors have considered that this has a male perspective and “gender” female. Also the life sciences are subject to gender inequality. But in the semiprivate level, women have had, and continue to play a fundamental role in the preservation and care of life. The purpose of this paper is the debate over the incorporation of this essential voice in bioethics ecological, that is, a bioethics that sees life in general, and their relationships, when discussing and analyzing ethical issues related to the life you name it.